2003
DOI: 10.2174/0929867033456648
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Synthetic Analogs: New Therapeutic Agents for Use in the Treatment of Diabetes Mellitus

Abstract: Glucagon-like peptide-1-(7-36)-amide (GLP-1) is a potent blood glucose-lowering hormone now under investigation for use as a therapeutic agent in the treatment of type 2 (adult onset) diabetes mellitus. GLP-1 binds with high affinity to G protein-coupled receptors (GPCRs) located on pancreatic β-cells, and it exerts insulinotropic actions that include the stimulation of insulin gene transcription, insulin biosynthesis, and insulin secretion. The beneficial therapeutic action of GLP-1 also includes its ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
105
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 170 publications
1
105
0
2
Order By: Relevance
“…Unlike GLP-1, exenatide exhibits extended kinetics 5 due to resistance to proteolytic degradation by dipeptidyl peptidase IV (DPPIV), and has up to 3000-fold higher in vivo potency for glucose-lowering in some animal models. 6 Agents that activate the GLP-1 receptor possess high therapeutic potential for the treatment of diabetes; [7][8][9] exenatide is a currently marketed antidiabetic agent that is shown to improve glycemic control in patients with type 2 diabetes. [10][11][12] Glucose-lowering with exenatide, GLP-1 and GLP-1 analogs has been associated with several mechanisms of action, the first of which to be identified was an enhancement of glucose-dependent insulin secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike GLP-1, exenatide exhibits extended kinetics 5 due to resistance to proteolytic degradation by dipeptidyl peptidase IV (DPPIV), and has up to 3000-fold higher in vivo potency for glucose-lowering in some animal models. 6 Agents that activate the GLP-1 receptor possess high therapeutic potential for the treatment of diabetes; [7][8][9] exenatide is a currently marketed antidiabetic agent that is shown to improve glycemic control in patients with type 2 diabetes. [10][11][12] Glucose-lowering with exenatide, GLP-1 and GLP-1 analogs has been associated with several mechanisms of action, the first of which to be identified was an enhancement of glucose-dependent insulin secretion.…”
Section: Introductionmentioning
confidence: 99%
“…The substitution of natural proteins by artificial sequences is a promising approach to resolve this issue. Recently, several therapeutic agents (Drucker, 2001;Drucker, 2002;Holz & Chepurny, 2003) have been proposed to increase www.intechopen.com insulinotropic effect of pancreatic cells and protect them from apoptosis. The most promising agent is glucagon-like peptide 1 (GLP-1) that has an extremely short half-life time (less than 2 min) in vivo (Lee et al, 2005).…”
Section: Poly(ethylene Glycol)-based Gelsmentioning
confidence: 99%
“…Glucagon-like peptide-1-(7-36)-amide (GlP-1), a hormone secreted by endocrine l cells of the intestinal tract, has unique insulinotropic and growth factor-like signal transduction properties, which make it a new therapeutic agent for the treatment of T2dM (19). recently, Magnusson et al showed that ZnT-8 is a potential target for the pharmacological manipulation of GlP-1 (20).…”
Section: Introductionmentioning
confidence: 99%